Driving factors for responsible sourcing in Europe: Motivations of renewable energy technology manufacturers - Kügerl, M.T.; Hitch, Michael; Gugerell, K. (2025)
The paper highlights the urgent demand for sustainable energy transitions within planetary boundaries while addressing social injustices. This transformation significantly relies on increasing the proportion of renewable energy sources, which requires extensive mining and utilisation of energy transition metals like copper, cobalt, and lithium. Particular concerns arise when Indigenous lands are involved in mining operations, raising issues of human rights and environmental integrity. The European Union and the United States of America have responded to these concerns with legislative measures to enhance supply chain transparency and prevent conflicts stemming from unethical practices. The study aims to explore responsible sourcing efforts among renewable energy technology manufacturers operating in Europe in the context of these regulations and the obstacles they encounter. Through semi-structured interviews with sustainability and procurement managers, the research investigates internal and external drivers for responsible sourcing, identifying altruistic values and regulatory compliance as critical factors. Despite acknowledging the importance of responsible sourcing, supply chain complexity and resource limitations persist. Ultimately, the study suggests that while responsible sourcing initiatives have the potential to promote justice within supply chains, there is a pressing need for holistic approaches to overcome existing barriers and effectively implement sustainable practices across the renewable energy sector.